Age-Specific Trends in Incidence, Mortality, and Comorbidities of Heart Failure in Denmark, 1995 to 2012. Issue 13 (28th March 2017) - Christiansen, Mia N.; Køber, Lars; Weeke, Peter; Vasan, Ramachandran S.; Jeppesen, Jørgen L.; Smith, J. Gustav; Gislason, Gunnar H.; Torp-Pedersen, Christian; Andersson, Charlotte
Abstract : Background: The cumulative burden and importance of cardiovascular risk factors have changed over the past decades. Specifically, obesity rates have increased among younger people, whereas cardiovascular health has improved in the elderly. Little is known regarding how these changes have impacted the incidence and the mortality rates of heart failure. Therefore, we aimed to investigate the age-specific trends in the incidence and 1-year mortality rates following a first-time diagnosis of heart failure in Denmark between 1995 and 2012. Methods: We included all Danish individuals >18 years of age with a first-time in-hospital diagnosis of heart failure. Data were collected from 3 nationwide Danish registries. Annual incidence rates of heart failure and 1-year standardized mortality rates were calculated under the assumption of a Poisson distribution. Results: We identified 210 430 individuals with a first-time diagnosis of heart failure between 1995 and 2012; the annual incidence rates per 10 000 person-years declined among older individuals (rates in 1995 versus 2012: 164 versus 115 in individuals >74 years, 63 versus 35 in individuals 65–74 years, and 20 versus 17 in individuals 55–64 years; P <0.0001 for all) but increased among the younger (0.4 versus 0.7 in individuals 18–34 years, 1.3 versus 2.0 in individuals 35–44 years, and 5.0 versus 6.4 in individuals 45–54 years; P <0.0001 for all). The proportion of patients with incident heart failure ⩽50 years of age doubled from 3% in 1995 to 6% in 2012 ( P <0.0001). Sex- and age-adjusted incidence rate ratios for 2012 versus 1996 were 0.69 (95% confidence interval, 0.67–0.71; P <0.0001) among people >50 years of age, and 1.52 (95% confidence interval, 1.33–1.73; P <0.0001) among individuals ⩽50 years of age; it remained essentially unchanged on additional adjustment for diabetes mellitus, ischemic heart disease, and hypertension. Standardized 1-year mortality rates declined for middle-aged patients with heart failure but remained constant for younger (<45 years) and elderly (≥65 years) patients. The prevalence of comorbidities (including diabetes mellitus, hypertension, and atrial fibrillation) increased, especially in younger patients with heart failure. Conclusions: Over the past 2 decades, the incidence of heart failure in Denmark declined among older individuals (>50 years), but increased among younger (⩽50 years) individuals. These observations may portend a rising burden of heart failure in the community. Abstract : Supplemental Digital Content is available in the text.